2021
DOI: 10.1007/s00432-021-03541-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological impacts of DNA methylation alterations on pancreatic ductal adenocarcinoma: prediction of early recurrence based on genome-wide DNA methylation profiling

Abstract: Purpose The present study was conducted to clarify the clinicopathological impacts of DNA methylation alterations on pancreatic ductal adenocarcinoma (PDAC). Methods Genome-wide DNA methylation screening was performed using the Infinium HumanMethylation450 BeadChip, and DNA methylation quantification was verified using pyrosequencing. We analyzed fresh-frozen tissues from an initial cohort (17 samples of normal control pancreatic tissue [C] from 17 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Moreover, among the genes included in Table 2 , only three showed a significant correlation between the levels of DNA methylation and expression ( P < 0.05 and r < −0.2 or r > 0.2) (Additional file 1 : Table S5). These findings are consistent with our previous studies, which revealed that even DNA methylation alterations at CpG sites not involved in regulating the expression of functionally important genes can become excellent surrogate markers for DNA methylation diagnostics [ 41 , 42 ]. Particularly at the carcinogenic risk stage, but not in established cancers, it is feasible that DNA methylation alterations would not yet have expanded immediately to involve important tumor-related genes [ 19 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, among the genes included in Table 2 , only three showed a significant correlation between the levels of DNA methylation and expression ( P < 0.05 and r < −0.2 or r > 0.2) (Additional file 1 : Table S5). These findings are consistent with our previous studies, which revealed that even DNA methylation alterations at CpG sites not involved in regulating the expression of functionally important genes can become excellent surrogate markers for DNA methylation diagnostics [ 41 , 42 ]. Particularly at the carcinogenic risk stage, but not in established cancers, it is feasible that DNA methylation alterations would not yet have expanded immediately to involve important tumor-related genes [ 19 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a mass spectrometry-based study [ 45 ], galectin 4, a group of carbohydrate-binding proteins involved in neoplastic development and progression, was identified as a down-regulated protein in short-term survivors of pancreatic cancer and correlated with an ER [ 46 ]. Genome-wide DNA methylation screening revealed that three CpG marker sites including a CpG site in CDK14 could predict an ER in formalin-fixed, paraffin-embedded surgically resected tissue [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for one of the marker molecules, CDK14, 112 was also found to serve as an adjunctive diagnostic tool for DNA methylation-based prediction of early recurrence. 111 Genome-wide DNA methylation analysis of blood samples from patients with LA before and after treatment with a tyrosine kinase inhibitor revealed that changes in DNA methylation profiles occur after treatment relative to the situation before treatment (unpublished data). In particular, using pretreatment blood samples, we were able to identify genes for which DNA methylation levels were significantly correlated with the response to treatment and disease-free survival (unpublished data), suggesting that measurement of DNA methylation levels in blood samples may be useful for prognostication.…”
Section: Dna Methylation Alterations As Biomarkersmentioning
confidence: 99%
“…103 based on their DNA methylation profiles, all patients showing early recurrence within 6 months after surgery were grouped only in a specific cluster. 111 Again, we analyzed both frozen tissue and FFPE specimens and developed a diagnostic panel for prediction of early recurrence that can be applied to FFPE specimens prepared routinely for pathological diagnosis. Immunohistochemistry for one of the marker molecules, CDK14, 112 was also found to serve as an adjunctive diagnostic tool for DNA methylation-based prediction of early recurrence.…”
Section: Dna Methylation Alterations As Biomarkersmentioning
confidence: 99%